Association between daily ambient temperature and drug overdose in Tokyo: a time-series study - Ananya Roy; Md Ashraful Alam; Yoonhee Kim; Masahiro Hashizume (Komiyama Printing Co. Ltd, 2022)
Background: Previous studies have reported that high ambient temperature is associated with increased risk of suicide; however, the association has not been extensively investigated with drug overdose which is the most common method of unsuccessful suicidal behavior in Japan. Therefore, this study aims to examine the short-term association between daily mean temperature and the incidence of self-harm attempts by drug overdose in Tokyo, Japan. Methods: We collected the emergency ambulance dispatch data and daily meteorological data in Tokyo from 2010 to 2014. A quasi-Poisson regression model incorporating a distributed lag non-linear function was applied to estimate the non-linear and delayed association between temperature and drug overdose, adjusting for relative humidity, seasonal and long-term trends, and days of the week. Sex, age and location-specific associations of ambient temperature with drug overdose was also estimated. Results: 12,937 drug overdose cases were recorded during the study period, 73.9% of which were female. We observed a non-linear association between temperature and drug overdose, with the highest risk observed at 21 °C. The highest relative risk (RR) was 1.30 (95% Confidence Interval (CI): 1.10-1.67) compared with the risk at the first percentile of daily mean temperature (2.9 °C) over 0-4 days lag period. In subgroup analyses, the RR of a drug overdose at 21 °C was 1.36 (95% CI: 1.02-1.81) for females and 1.07 (95% CI: 0.66-1.75) for males. Also, we observed that the risk was highest among those aged ≥65 years (RR = 2.54; 95% CI: 0.94-6.90), followed by those aged 15-34 years (RR = 1.25; 95% CI: 0.89-1.77) and those aged 35-64 years (RR = 1.15; 95% CI: 0.78-1.68). There was no evidence for the difference in RRs between urban (23 special wards) and sub-urban areas in Tokyo. Conclusions: An increase in daily mean temperature was associated with increased drug overdose risk. This study indicated the positive non-linear association between temperature and incomplete attempts by drug overdose. The findings of this study may add further evidence of the association of temperature on suicidal behavior and suggests increasing more research and investigation of other modifying factors.